GEOMETRIC COMMUNICATION SKILLS PROFILE OF MTS STUDENTS IN CONTENT LINES AND ANGLES - HARTATIANA HARTATIANA (Sriwijaya University Learning and Education International Conference, 2016)
Learning math is a social activity (social activity). As mathematics itself, inseparable from mathematics learning social activities. Unfortunately, traditional learning forget the social nature of learning in mathematics. Mathematical communication is an important component in learning mathematics, tool to exchange ideas, and to clarify the understanding of mathematics. The importance of communication skills in mathematics because mathematics is essentially a language filled with notations and terminology so that the concepts that form can be understood by students if it has mathematical communication skills, but the ability of mathematical communication is often overlooked. Communication is part of the geometric mathematical communication skills. Geometric communication plays an important role in improving the understanding not only related to the topic of geometry alone. This paper describe how geometric communication ability MTs students. The test results are given indicates 5% have aexcellent geometric communication skills, 18% good, 42% medium, 25% less and 10% are very less. From the answers given students' communication skills geometric limitations shown by the students answered questions tend to be brief, without the process of how to get it. For better results the authors suggest teachers should apply the model of student-centered learning, so that students can be actively involved in learning and provide opportunities for students to communicate his ideas.